Finite-Time Trajectory Tracking for Wheeled Mobile Robot - Banerjee A.; Taslima E.; Pandey V.; Diana B.; Kamal S.; Xiong X. (My University, 2025)
This paper presents a comprehensive exploration of the implementation of a finite-time control technique for wheeled mobile robots (WMRs). Finite-time control offers a promising avenue for achieving rapid and precise trajectory tracking in dynamic environments, making it particularly suitable for applications requiring agile and responsive robot motion. This paper encompasses designing and implementing a finite-time control algorithm through Lyapunov stability theory tailored to the dynamics of WMRs. We evaluate the performance of finite-time control through simulation and real-world experiments on Quanser’s Qbot Platform, assessing its ability to achieve desired trajectory tracking. The insights gained from this research contribute to the advancement of control methodologies for WMRs, with potential applications in autonomous navigation, mobile robotics, and industrial automation. © 2024 IEEE.